Critical Care Neurology Perspective on Delirium - Maas, Matthew B.; Naidech, Andrew M. (Seminars in Neurology, 2016)
The evidence linking delirium to poor outcomes after critical illness is compelling, including higher mortality, prolonged mechanical ventilation, longer length of intensive care unit stay, and long-term cognitive impairments. The attitude toward delirium in the neurologic community is shifting away from viewing it as an unmodifiable, inevitable consequence of severe illness to treating it is as a neurologic emergency, akin to seizures or encephalitis. Delirium, like other manifestations of critical illness encephalopathy, is an organ dysfunction syndrome. Given the brain's central role in maintaining homeostasis, brain failure may dysregulate many downstream functions of significant consequence in critically ill patients. The diagnosis of delirium may be confounded in patients with primary brain disorders, but nevertheless delirium symptoms in the neurologic population are also independently associated with worse outcomes. There is scant evidence for directed pharmacological treatment of delirium, but multicomponent care bundles that address the management of pain, agitation, sedation, and delirium are effective at reducing the burden of delirium in the general intensive care unit population. The management of delirium in the neurologic intensive care environment is mostly extrapolated from studies on general medical critical illness and noncritically ill neurologic patients. Further investigation into the unique risks and management needs of critically ill neurologic and neurosurgical patients is needed to reduce the burden of delirium in that population.
Keywords: delirium; encephalopathy; critical care; neurologic; neurocritical care